2023
DOI: 10.1128/spectrum.04664-22
|View full text |Cite
|
Sign up to set email alerts
|

Specific Plasma MicroRNA Signatures Underlying the Clinical Outcomes of Hepatitis E Virus Infection

Abstract: There is increasing evidence that viruses dysregulate the expression and/or secretion of microRNAs to promote viral replication, immune evasion, and pathogenesis. In this study, we evaluated the change in microRNA abundance in patients with acute or chronic HEV infection and asymptomatic HEV-infected blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…They identified miR-450b as a significant indicator of mortality in acute liver failure amongst HEV-infected pregnant women[ 145 ]. Consistent with this, miRNA profiling shows that miRNAs circulating in HEV-infected patients’ plasma could indicate self-resolving acute and chronic hepatitis E, as well as acute liver failure[ 146 , 147 ].…”
Section: Viral Factors Affecting Liver Failurementioning
confidence: 69%
See 1 more Smart Citation
“…They identified miR-450b as a significant indicator of mortality in acute liver failure amongst HEV-infected pregnant women[ 145 ]. Consistent with this, miRNA profiling shows that miRNAs circulating in HEV-infected patients’ plasma could indicate self-resolving acute and chronic hepatitis E, as well as acute liver failure[ 146 , 147 ].…”
Section: Viral Factors Affecting Liver Failurementioning
confidence: 69%
“…Furthermore, miRNA signatures identified in patients’ sera could link with hepatitis E-specific immune dysfunction[ 146 , 148 ]. It is noted that miRNAs can be packed in exosomes, which HEV virion particles use for egress[ 44 ].…”
Section: Viral Factors Affecting Liver Failurementioning
confidence: 99%
“…Li et al [41] reported that the anti-cancer drug gemcitabine inhibited HEV through inducing an interferon-like response via the activation of STAT1 phosphorylation. Human liver-derived organoids [42,43] and microRNA signatures in HEV infection [44,45] could be helpful for the development of antivirals against HEV infection.…”
Section: Discussionmentioning
confidence: 99%